Синтрон Софійського собору в Києві - Архипова, Є.І. (Археологія, 2000)
За даними археологічних досліджень 1940, 1950 і 1952рр. та сучасного вивчення пам’ятки пропонуються можливі варіанти відтворення оздоблення синтрону і влаштування трону митрополита в Софійському соборі в Києві, що неодноразово реставрувався ще в домонгольські часи. Синтрон Софийского собора в Киеве, как и сам собор, за более чем 900-летнюю историю его существования неоднократно поновлялся и реставрировался. Изучение сохранившихся деталей его декора и материалы археологического исследования памятника позволяют воссоздать конструкцию и характер убранства древнего синтрона, а также говорят о его ремонтах еще в домонгольское время. К ранней истории собора относится устройство каменного трона митрополита из плит красного шифера, инкрустированных смальтой, с размещением композиции с Голгофским крестом и подсвечниками в центре синтрона. К XII— XIII в. можно отнести устройство спинки кресла из мраморной плиты с рельефом конца X—XI в., инкрустированной смальтой и мрамором. Во время ремонтов XVII—XIX в. был изменен профиль скамьи синтрона, ставшего вместо двухступенного трехступенным; утраты в мозаичном наборе декоративных панно фриза над скамьей реставрированы керамическими поливными плитками; переставлены и дополнены мраморные плиты облицовки. На смену металлическому креслу XVII в. в XIX в. кресло митрополита собрали из сохранившихся деталей предыдущих эпох: мраморная спинка и шиферные подлокотники. В таком виде оно и дошло до нашего времени. The synthrone of the Sophia Cathedral in Kyiv was repeatedly renewed and restored along with the Cathedral itself during its 900-year-old history. Study of the kept details of its decor and the materials of archeological investigation of the site allow one to re-create the construction and the character of decoration of the ancient synthrone and testify to its repairs as early as in the pre-Mongolian age. The structure of the metropolitan’s stone throne made of plates of red slate, which are encrusted with smalto, and the allocation of the composition with the Calvary cross and candlesticks at the center of the synthrone is related to the early history of the Cathedral. To the XII—XIII centuries AD, we can refer the armchair back made of a marble slab with the relief dated back to the end of the X—XI centuries AD, which was encrusted with smalto and marble. During repairs in the XVII-XIX centuries AD, the profile of the synthrone bench was changed, and it became three-stage instead of a two-stage one, the losses in the mosaic composition of the decorative panel of the frieze above the bench were restored with ceramic enamelled plates; marble slabs of the facing were displaced and completed. Instead of a metal armchair of the XVII century AD, the metropolitan’s armchair was assembled in the XIX century by using the kept details of the previous ages, namely, the marble back and slate arm rests. It has come to us in such a view.